Ritual midodareni sebagai medium spiritualitas Kristen: Perspektif triad-theological Steven Jack Land - Andreas Budi Setyobekti (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
Midodareni, carried out in preparation for marriage, still needs to be understood in Christian theology. Midodareni is a Javanese tradition that must be eliminated after someone believes in Jesus. This tension between Christian faith and culture continues into the modern era. If it continues to be preserved, culture will be eliminated and replaced with religious 'culture'. Therefore, an analysis of symbols, activities, and philosophy is needed to be used as a medium for Christian spirituality. This research examines Midodareni's wedding preparations from the perspective of Steven Jack Land's theological triad. The research method used for analysis describes the midodareni tradition with Steven Jack Land's theological triad approach. The research results show that not all midodareni preparations can be applied to Christian wedding preparations. Some processes can be carried out by transforming meaning, but others cannot. Midodareni has implications for society to encourage harmony and holistic education for bridal couples. AbstrakMidodareni dilakukan untuk persiapan pernikahan masih kerap disalahpahami dalam teologi Kristen. Midodareni dianggap sebagai tradisi Kejawen yang harus dihilangkan setelah seseorang percaya kepada Yesus. Ketegangan antara iman Kristen dan budaya ini terus bergulir hingga era modern ini; jika terus dipertahankan, maka budaya menjadi tersingkirkan dan digantikan dengan ‘budaya’ agama. Oleh karena itu, diperlukan analisis terhadap simbol-simbol, aktivitas-aktivitas, dan filosofi untuk dijadikan sebagai medium spiritualitas Kristen. Tujuan penelitian ini untuk mengkaji persiapan pernikahan Midodareni dari perspektif triad theological Steven Jack Land. Metode penelitian yang digunakan adalah analisis deskriptif tentang tradisi midodareni dengan pendekatan triad theological Steven Jack Land. Hasil penelitian menunjukkan bahwa persiapan midodareni tidak semuanya dapat diterapkan dalam persiapan pernikahan iman Kristen. Ada prosesi yang dapat dilakukan dengan mentransformasi maknanya, ada juga yang sama sekali tidak perlu dilakukan. Midodareni berimplikasi kepada peran komunitas untuk mendorong keharmonisan dan pendidikan holistik bagi pasangan mempelai.